Use of placebos and post-trial benefits - Perlingeiro, Ricardo; Arruda, Carmen Silvia (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Brazilian legislators have not yet enacted any laws regarding the use of placebos and the duties of assistance to research subjects. As a result of this omission, public administrative authorities have to deal with the subject on a regular basis, oriented by fundamental rights and judicial supervision. Against that backdrop, CNS (National Health Council)2, speaking through CONEP (National Research Ethics Committee)3, ANVISA (Healthcare Surveillance Agency)4, the CFM (Federal Medical Council)5, the CNJ (National Justice Council)6 and the STF (Federal Supreme Court)7 have expressed their opinions on the subject in a consistent manner. [...]